2007
DOI: 10.1002/dneu.20523
|View full text |Cite
|
Sign up to set email alerts
|

Activation of matrix metalloproteinase‐3 is altered at the frog neuromuscular junction following changes in synaptic activity

Abstract: The extracellular matrix surrounding the neuromuscular junction is a highly specialized and dynamic structure. Matrix Metalloproteinases are enzymes that sculpt the extracellular matrix. Since synaptic activity is critical to the structure and function of this synapse, we investigated whether changes in synaptic activity levels could alter the activity of Matrix Metalloproteinases at the neuromuscular junction. In particular, we focused on Matrix Metalloproteinase 3 (MMP3), since antibodies to MMP3 recognize m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 31 publications
0
19
0
Order By: Relevance
“…Interestingly, MMP‐3 is expressed by PSCs at the NMJ and its expression is tightly regulated according to innervation state (VanSaun et al . ). Moreover, persistence of agrin due to genetic deletion of MMP‐3 leads to the preservation of endplates following nerve injury and degeneration (Chao et al .…”
Section: Als‐related Electrophysiological Changes In Mns and Nmjsmentioning
confidence: 97%
See 1 more Smart Citation
“…Interestingly, MMP‐3 is expressed by PSCs at the NMJ and its expression is tightly regulated according to innervation state (VanSaun et al . ). Moreover, persistence of agrin due to genetic deletion of MMP‐3 leads to the preservation of endplates following nerve injury and degeneration (Chao et al .…”
Section: Als‐related Electrophysiological Changes In Mns and Nmjsmentioning
confidence: 97%
“…Second, since agrin levels are controlled in part through degradation by matrix metalloproteinases (MMPs) (Darabid et al 2014), PSCs may regulate agrin levels by changing their secretion of MMPs. Interestingly, MMP-3 is expressed by PSCs at the NMJ and its expression is tightly regulated according to innervation state (VanSaun et al 2007). Moreover, persistence of agrin due to genetic deletion of MMP-3 leads to the preservation of endplates following nerve injury and degeneration (Chao et al 2012) and modulation of neuronal MMP-9 levels significantly delays muscle denervation (Kaplan et al 2014).…”
Section: Molecular and Age-dependent Interactions At The Nmj In Alsmentioning
confidence: 99%
“…A previous study has shown that serum levels of MMP3 are increased in GMG patients [9]. Our subgroup of 19 patients may have an increased risk of developing a more generalized and severe MG. MMP3 degrades agrin [34], and reduced synaptic activity downregulates its activity [22]. MMP-induced changes in agrin concentration and function can therefore lead to disturbances in agrin-mediated maintenance of the neuromuscular junction.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have suggested MMP9 to be an important factor in multiple sclerosis (MS) [18]. MMP2 and MMP3 activate MMP9 [19,20,21], and MMP2 and MMP9 are potent activators of MMP3 [22]. …”
Section: Introductionmentioning
confidence: 99%
“…However, one could hypothesize about their role in regulating agrin levels through MMP-MMP interaction. We know that MMP-2 and MMP-3 are able to activate MMP-9 [54,55,56,57], whereas MMP-2 and MMP-9 are potent activators of MMP-3 [58]. Agrin is a substrate for MMP-3 [59].…”
Section: Serum Levels Of Mmps In Mgmentioning
confidence: 99%